2020
DOI: 10.1177/0300891620933678
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary malignancies involving lung cancer: a single-center experience

Abstract: Objective: Currently, unlike earlier years, patients affected by multiple primary malignancies (MPM) are significantly increased, thus representing a clinical-pathologic category worthy of attention. Their clinical features and prognosis still need to be studied thoroughly, and this is the aim of our study. Methods: Patients with MPM involving lung cancer admitted in our center between January 2006 and December 2016 were considered. Parametric and nonparametric testing was used for statistical comparisons. Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…In our cohort of patients, we noticed a relatively high incidence of previous cancers (38.9%) 22 . We investigated these data among different institutions, but no clear explanation could be drawn.…”
Section: Commentmentioning
confidence: 83%
See 1 more Smart Citation
“…In our cohort of patients, we noticed a relatively high incidence of previous cancers (38.9%) 22 . We investigated these data among different institutions, but no clear explanation could be drawn.…”
Section: Commentmentioning
confidence: 83%
“…In our cohort of patients, we noticed a relatively high incidence of previous cancers (38.9%). 22 We investigated these data among different institutions, but no clear explanation could be drawn. We can speculate that this relative incidence of previous cancers might be explained with a more careful follow-up ruled out in these patients compared to the general population.…”
Section: Commentmentioning
confidence: 99%
“…Moreover, breast adenocarcinoma, lung cancer and prostate adenocarcinoma accounted for the most represented PC; these data are in line with those reported by Song and colleagues [ 16 ] based on the Surveillance, Epidemiology and End Results database. Conversely, Liu et al [ 17 ] and Donin et al [ 18 ] found a higher proportion of cancers from the upper aerodigestive tract, whereas Ventura et al [ 9 ] reported a higher incidence of cancers from the urogenital system.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study [ 8 ] reported that lung cancer was the most frequently diagnosed second primary cancer among cancer survivors in the USA. A frequency of up to 22% has been described so far [ 9 ], but the exact percentage of patients with multiple cancers varies widely because the different reports based their selection of patients and their surveillance protocol on the type of cancer and on the respective reimbursement systems of each national health system. Moreover, differences in ethnicity in the analysed cohort of patients also have a strong influence on the epidemiology of cancers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of multiple primary cancers is influenced by a number of factors, including the chronological nature of tumorigenesis ( 24 ). In a study by Ventura ( 25 ) on patients with lung cancer combined with other solid tumors, it was shown that patients with heterochronic multiple primary cancers had a higher risk of death than those with simultaneous multiple primary cancers. This may be due to the weakening of the body’s immune function as a result of receiving multiple anti-tumor treatments within a short period of time or at the same time.…”
Section: Discussionmentioning
confidence: 99%